Fostering Nurses' Moral Agency and Moral Identity: The Importance of Moral Community. (September 2016) - Liaschenko, Joan; Peter, Elizabeth
Abstract: It may be the case that the most challenging moral problem of the twenty‐first century will be the relationship between the individual moral agent and the practices and institutions in which the moral agent is embedded. In this paper, we continue the efforts that one of us, Joan Liaschenko, first called for in 1993, that of using feminist ethics as a lens for viewing the relationship between individual nurses as moral agents and the highly complex institutions in which they do the work of nursing. Feminist ethics, with its emphasis on the inextricable relationship between ethics and politics, provides a useful lens to understand the work of nurses in context. Using Margaret Urban Walker's and Hilde Lindemann's concepts of identity, relationships, values, and moral agency, we argue that health care institutions can be moral communities and profoundly affect the work and identity and, therefore, the moral agency of all who work within those structures, including nurses. Nurses are not only shaped by these organizations but also have the power to shape them. Because moral agency is intimately connected to one's identity, moral identity work is essential for nurses to exercise their moral agency and to foster moral community in health care organizations. We first provide a brief history of nursing's morally problematic relationship with institutions and examine the impact institutional master narratives and corporatism exert today on nurses' moral identities and agency. We close by emphasizing the significance of ongoing dialogue in creating and sustaining moral communities, repairing moral identities, and strengthening moral agency .